Diseño de una máquina para separar los granos de garbanzo de la vaina de la especie Kabuli (2021)
This project seeks to design a machine for separating chickpea grains of the Kabuli species in order to reduce the separation time and obtain an adequate separation for the product, since many farmers perform the separation manually and this can cause physical problems, in addition to not meeting the demand. First, the product to be worked was characterized, investigating its physical properties, morphology, humidity, how they are grown and in which countries it is produced most frequently. The state of chickpea production in Colombia was also consulted to find out in which departments this production is carried out. An analysis was carried out on which components are more suitable for the machine and can perform adequately together, taking into account existing machines that perform the separation of legumes similar to chickpea.